The effects of turmeric on the grain structure and properties of copper electrodeposited composites. (1st November 2020) - Merrill, R.; Wu, L.; Graves, J. E.; Beddow, J.; Fuentes, E.; Cobley, A.
ABSTRACT: The objective of this research was to electrocodeposit turmeric particles into copper matrices, and assess the influence of turmeric on the microstructure and properties of those deposits. The incorporation of turmeric had a significant effect on both the grain structure and properties of the copper deposits, with turmeric particles of a Z-average size of 289 ± 30 and 278 ± 15 nm having a greater influence on grain refinement than particles of 134 ± 37 nm, even at much lower deposit particle contents. The incorporated turmeric increased both the hardness and water contact angle of the deposits; however, a reduction in resistance to salt spray corrosion was also observed.